PROJECT-BASED LEARNING IN INDONESIAN EFL CLASSROOMS: FROM THEORY TO PRACTICE - Yustinus Calvin Gai Mali (IJEE (Indonesian Journal of English Education), 2016)
Project based learning (PBL) refers to an approach to instruction that teaches curriculum concepts through a project espousing principles of learner-centered teaching, learner autonomy, collaborative learning, and learning through tasks. This paper justifies the implementation of PBL to design two main projects and their activities in Creative Writing and Second Language Acquisition classes at English Language Education Program of Dunia University Indonesia (ED-DU). Moreover, the paper details pedagogical practices and learning resources deployed in both classes. The discussions would seem to indicate that the use of PBL grounded in the projects shows a high level of students’ participation in learning, and teachers’ innovative teaching practices. Finally, the paper hopes to provide EFL teachers who have similar teaching practices with practical ideas they can modify and develop to help students achieve particular learning objectives in their classrooms and continue the positive trends of implementing PBL in teaching and learning.